Rebalancing the patient experience: 20 years of a pendulum swing - Tiffany Christensen (The Beryl Institute, 2017)
This essay looks back at two decades of the patient experience movement. The evolution of patient experience includes moving from a belief system in which patients and families are solely the recipients of care to a model in which patients and families are co-designing treatment plans, systems and policies. This evolution has taken time and continues to evolve to this day. As the pendulum swings, we see that we have made great progress and, simultaneously, found ourselves with all new challenges to overcome.